Respuesta :

Answer:

{1}

Step-by-step explanation:

We find determinant for the given matrix and set it equal to -1

To find determinant we apply formula

[tex]|A| = a_{11}(a_{22}a_{33} − a_{32}a_{23}) - a_{12}(a_{21}a_{33} − a_{31}a_{23})+a_{13}(a_{21}a_{32} - a_{31}a_{22})[/tex]

[tex]|A| = x(1x - 2) - 0(7-7) + 0(14-7x) [/tex]

|A| = x^2 - 2x

Now we set the determinant = -1

[tex]x^2 - 2x=-1[/tex]

Add 1 on both sides

[tex]x^2 - 2x + 1=0[/tex]

Now factor it

(x-1)(x-1) = 0

Set each factor =0  and solve for x

x- 1=0 so x=1